Classdojo Interactive Media To Enhance Students' Conceptual Understanding In Mathematics - Dida Hartati , Dida Hartati; Nurdin Muhamad; Ani Siti Anisah (Jurnal PGMI UNIGA, 2025)
This research aims to improve the mathematical concept understanding of first-grade students at SD GIS Prima Insani through the use of ClassDojo interactive media. Using a quantitative experimental method, the study involved 55 students divided into an experimental class (n=26) and a control class (n=29). Pretest results indicated that the initial abilities of both groups were equivalent (p = 0.527). However, after the intervention, the Mann-Whitney test revealed a significant difference in posttest scores with an Sig. 0.038 < 0.05 The result N-Gain score of 0.57 indicates a "medium" improvement category with an effectiveness level of 57%. Furthermore, student engagement increased significantly from 60% to 90% when using ClassDojo. These findings are supported by constructivist theory, which emphasizes active student involvement. It is concluded that ClassDojo interactive media is effective in enhancing mathematical concept understanding and creating a more interactive and meaningful learning experience compared to conventional media. Keywords: ClassDojo, Interactive Media, Concept Understanding, Mathematics.